queer_Format : Gewerkschaftsmagazin für Lesben und Schwule, Bisexuelle und Transgender. (Berlin : ver.di, 2005)
Fonds Suzan Daniel (FSD)
Periodiciteit : onbekend
Redactie : Paule-Thiede-Ufer 10, 10179 Berlin
Duits
Periodiek